Access to credit and the expansion of broadband internet in Peru - Antonio Cusato Novelli; José Luis Castillo Mezarina (Inter-American Development Bank (IDB), 2023)
We exploit the staggered expansion of the internet broadband network to firms and bank branches locations in Peru during the last decade to study non-financial firm performance and bank credit dynamics. Access to broadband unleashes firm growth, increases the chances of entry of firms and reduces the probability of exit in benefited locations. For those firms that had a borrowing relation with a bank before the expansion of broadband, the increase in sales serves as a signal to banks about their profitability, which in turn respond by providing more credit. Entry and exit from the credit market follows a similar pattern as in the case of firms, but the results take longer to materialize after the shock. We can disentangle supply and demand effects, since there is a group of firms and bank branches with different locations and asymmetrical timing for the availability of the technology. Our analysis highlights the importance of the demand channel in the reduction of the observed interest rates, which is consistent with the fact that our credit market results are concentrated among micro and small firms, and firms with thin credit files, which are often perceived as riskier
Keywords: O33; L86; G21; 330; Broadband internet; Technological change; Banks; Credit